Law and Justice in the Phenomenology of J.-L. Marion - Roggero, Jorge Luis (2024)
This paper aims to give an account of the general outlines of a possible Phenomenology of Law in the work of Jean-Luc Marion, based on an inquiry into the notions of legal phenomenon and justice.